Hubungan Motivasi Dengan Kinerja Perawat Rawat Inap Di Rumah Sakit Islam Ibnu Sina Payakumbuh Tahun 2022 - Ilayani Ilayani; Meri Herliza; Elsa Luvia Harmen (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2023)
Motivation performance at RSI Ibnu Sina Payakumbuh is low, supported by results of interviews with the head of the inpatient ward who stated that motivation was low and performance was also low even though therewere some who stated that the performance of nurses was quit good, so the reseaarchers wanted to see therelationship between motivation and the performance ofnurses whose sample was 44 nurses. The design of thisresearch is a cross sectional study, with an analiytical observational approach, using a questionnaire to obtain research data and the type of research is quantitative. The data in this study is primary with total sampling. Dataanalysis teachningques used univariate and bivariate analysis, data processing using spss software and Microsoft excel.The results showed that as many as 28 nurses (64%) stated low motivation and 39 nurses (87%) stated low. Motivation and performance have a relationship, a significant value of 0.141 is smaller than 0.05mased on the results of these studies, it is expected that the management of RSI Ibnu Sina Payakumbuh pays moreattention to the motivation of nurses, motivation is a psychological factor to foster enthusiasm and motivation at work